Teachers’ Motivation for Professional Development: A Phenomenological Case Study Approach - Dominic Siami Egure (Scientia Publica Media, 2026)
The rapid transformation of the education sector, driven by advances in AI and evolving student needs, makes continuous professional development (PD) essential for teachers; yet, sustaining motivation for ongoing learning remains a significant challenge in resource-constrained contexts like Nigeria. This qualitative study explores how teachers in the ECHO Education Nigeria PD program perceive the value of their learning experiences and identifies the factors that motivate or discourage their participation and continued growth. Using a phenomenological case study design, data were collected through in-depth interviews with eight of the ten highest-scoring participants from a Value Creation Survey completed by more than sixty teachers. Findings reveal three main categories of motivational influences: factors that propel engagement, such as teachers’ desire to make a meaningful impact on their students and society and their commitment to staying current in their profession; factors that sustain engagement, including the mutual respect and sense of belonging fostered within the EEN PD social learning community and the resulting shifts in perception and teaching practice; and factors that hinder engagement, such as limited access to teaching resources, preference for in-person interaction, lack of administrative support, and broader systemic challenges within the education system. The study underscores the importance of both intrinsic and extrinsic motivators and emphasizes the need for professional development models that are collaborative, accessible, and responsive to local realities. Implications for educational leadership and policy include fostering supportive school cultures, improving technological access, and addressing systemic barriers to teachers’ ongoing development.